The Role of Pesantren Education in Overcoming Bullying among Female Santri: A Phenomenological Perspective - Takdir, Mohammad; Mumayyizah, Fashatul; Mubarridah, Shaimatul (INSTED: Interdisciplinary Studies in Education & Society, 2025)
A psychological issue faced by pesantren is the prevalence of bullying among female santri. This study aims to examine the determinants of bullying behavior and the role of pesantren in addressing this issue at the Annuqayah Islamic boarding school. Employing a qualitative research design with a phenomenological approach, the researchers utilized observation, interviews, and documentation methods for data collection in the field. The findings reveal several factors contributing to bullying among female santri, including familial influences, prior victimization, peer pressure, and inherent bullying traits. This study demonstrates that pesantren Annuqayah plays a significant role in addressing bullying behawior among female santri by educating both perpetrators and victims of bullying, establishing regulations prohibiting such behavior, administering penalties to offenders, conducting discussions on the dangers of bullying in pesantren, and providing Kiai guidance to foster positive conduct among female santri.